2021
DOI: 10.1021/jasms.0c00430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ambient Vapors Present in an Electrospray Ionization Source on Gas-Phase Ion Structures

Abstract: According to current consensus, structures of protomeric (or deprotomeric) tautomers of gaseous ions generated by electrospray ionization depend primarily on the nature of the spray solvent. To probe the effect of the spray solvent on protonation, 4-aminobenzoic acid (PABA) has often been selected as the model compound. It is widely accepted that the protonation in the gas phase takes place primarily on the carbonyl oxygen atom when the sample is sprayed in methanol and on the nitrogen atom when acetonitrile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…14,15 This solvent-dependent protonation-site switching is not only found in BC but prevails in other (bio-)organic molecules. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Much effort has been devoted to microsolvated clusters, in which an ion is solvated by a few to several hundreds of molecules, 14,[34][35][36] because the degree of solvation can be tuned by controlling the type and numbers of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 This solvent-dependent protonation-site switching is not only found in BC but prevails in other (bio-)organic molecules. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Much effort has been devoted to microsolvated clusters, in which an ion is solvated by a few to several hundreds of molecules, 14,[34][35][36] because the degree of solvation can be tuned by controlling the type and numbers of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, infrared photodissociation spectroscopy (IRPD) and ion mobility mass spectrometry (IMS) have frequently been applied to assign protomers of desolvated ions. [8][9][10][12][13][14][15][16][17][18][19][20][21][23][24][25][26][27]30,[32][33][34][35] For example, the protomers of isolated H + BC could clearly be separated by both IRPD and IMS. 15 In principle, IMS can separate isomers based on the collision cross section (CCS) with inert buffer gas, which strongly depends on charge distribution and shape of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that solvents affect the formation of tautomers detected by IM-MS. − Chandran et al found solvent effects must be thoroughly evaluated before a validated “standard” protocol for the quantitative determination of an analyte can be developed and recommended. In addition, Morsa et al detected the mobility peaks of acetonitrile adducts of electrophilic benzylium cations using the electrospray ionization source by trapped ion mobility spectrometer (TIMS).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] For this purpose, highresolution mass spectrometry is particularly useful because the high resolving power enables discrimination of so-called isobaric ions with different exact masses. 28 For this purpose, high-throughput biochemical techniques that do not require time-consuming elaborate sample preparation or chromatographic procedures for analysis are more attractive. The laser diode thermal desorption coupled with atmospheric pressure chemical ionization mass spectrometry (LDTD-APCI-MS) is a promising technique for rapidly determining the composition of biofluids.…”
Section: Introductionmentioning
confidence: 99%